Dynamics of a Two-Dimensional Cooperative System of Polynomial Difference Equations With Cubic Terms - Bektešević, Jasmin; Hadžiabdić, Vahidin; Mehuljić, Midhat; Mujić, Naida (Sarajevo Journal of Mathematics, 2024)
In this paper we present a local dynamics and investigate the global behavior of the following system of difference equations $x_{n+1}=ax_{n}^{3}+by_{n}^{3}$ $y_{n+1}=Ax_{n}^{3}+By_{n}^{3}$ $n\in\mathbb{N}_0$ with non-negative parameters and initial conditions $x_{0}$ and $y_{0}$ that are real numbers. We establish the relations for local stability of equilibriums and necessary and sufficient conditions for the existence of period-two solution(s). We then use this result to give global behavior results for special ranges of parameters and determine the basins of attraction of all equilibrium points.